PTU-144 EUS in The Diagnosis and Staging of Lung Cancer: Single Centre Experience at Glasgow Royal Infirmary. (17th August 2016) - Harrington, C; Paterson, S; Stanley, A
Abstract : Introduction: Lung cancer is the leading cause of cancer related death in the Western World. 1 Accurate staging is required to identify those patients with localised Non Small Cell Lung Cancer (NSCLC) who have resectable disease. Patients with Small Cell Lung Cancer (SCLC) or T4, N2-3 or M1 NSCLC are not suitable for surgery. Endoscopic ultrasound (EUS) with fine needle aspiration (FNA) can help obtain a tissue diagnosis where Endobronchial Ultrasound (EBUS)-FNA or CT guided biopsy is not possible. 2 Methods: We performed a retrospective search of prospectively recorded data on all patients who were referred for EUS-FNA between 2012 and 2015 for the following indications: Suspicious lung mass with or without associated lymphadenopathy. This group has been subdivided into those who underwent EUS-FNA to obtain a tissue diagnosis and those who already had a tissue diagnosis and the EUS-FNA was performed for tumour staging. Suspicious mediastinal or epigastric lymph nodes alone. This group has been subdivided into those for whom EUS-FNA was performed to investigate possible recurrence of previously resected lung cancer and those who had unexplained mediastinal or epigastric lymphadenopathy. Procedure: The EUS-FNA procedures were all undertaken by AJS or SP, with a 22 g FNA needle (Cook Ltd), using a standard linear echoendoscope with ultrasound (Pentax Ltd & Hitachi Ltd). We collected data on patient demographics, EUS findings and procedures, cytology and prior pathology and radiology using our electronic clinical reporting system Results: 35 patients were referred for EUS-FNA for the diagnosis or staging of lung cancer during the study period. 2 patients were unsuitable candidates. 25 patients had a suspicious lung mass and 8 had suspicious lymph nodes alone. In the group with a suspicious lung mass, EUS-FNA led to a diagnosis of lung cancer in 15 patients with 7 patients having benign pathology. 3 patients already had a diagnosis of lung cancer; EUS-FNA led to upgrading of tumour stage in 1 patient. In the group with suspicious lymph nodes alone, 3 diagnoses of lung cancer were made. Of the remaining 5 patients, 4 had benign pathology and 1 had gastric cancer. No procedural complications were encountered in any patient. EUS-FNA therefore led to a diagnosis of lung cancer in 60% (18/30) of the cases referred without a prior diagnosis. Conclusion: EUS-FNA is a useful modality in the diagnosis and staging of lung cancer when EBUS and/or CT guided biopsy fail to obtain a tissue diagnosis. References: 1 Ferlay J, Shin HR, Bray F, et al . Estimates of worldwide burden of cancer in 2008: GLOBOCAN 2008. Int J Cancer . 2010 ;127:2893–917. 2 Colella S, Vilmann P, Konge L, et al . Endoscopic ultrasound in the diagnosis and staging of lung cancer. Endoscopic Ultrasound . 2014;3 (4):205–212. Disclosure of Interest: None Declared